GOLDEN SECTION SEARCH AND HYBRID TABU SEARCH-SIMULATED ANNEALING FOR LAYOUT DESIGN OF UNEQUAL-SIZED FACILITIES WITH FIXED INPUT AND OUTPUT POINTS - Jeong, Donghwa; Seo, Yoonho (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
The facility layout problem involves the positioning of facilities in order to minimize the total travel distance. This study deals with a layout design of unequal-sized facilities with fixed input and output points. Since a mixed integer programming model cannot solve large-sized problems in a reasonable computational time, a heuristic algorithm composed of a placing method based on golden section search and a hybrid tabu search-simulated annealing is developed. In the placing method, facilities are sequentially arranged by a given sequence and the optimal coordinates of facilities are determined using the golden section search. To find the sequence that yields the minimum total travel distance, the hybrid tabu search-simulated annealing is developed. Computational experiments show that the proposed algorithm generates the optimal layout result for test problems with less than 6 facilities and improves the best known results from Xiao et al.(2013) in a shorter time.